(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this paper, the tuning design of SSSC and PSS was examined in increasing the damping of system oscillations and improve the stability of the power system during disturbances. The design problem of the SSSC controller and PSS is designed as problem of optimization and the technique uses (PSO) technique to find for optimal control parameters. By minimizing the objective function based on the speed deviation and time domain, which deliberately deviates at the oscillation angle of the alternator rotor to improve performance of transient stability of the system. The proposed controllers are tested on the system of weak bonding ability exposed to severe disturbance. Nonlinear simulation results are presented to demonstrate the proposed controller’s effectiveness and its ability to give efficient damping. It is also noted that the proposed controllers of SSSC and PSS greatly improves the power system stability.